Estimating belowground nitrogen inputs of pea and canola and their contribution to soil inorganic N pools using ¹⁵N labeling - Arcand, Melissa M.; Knight, J. Diane; Farrell, Richard E. (Plant and soil, 2013)
Background and aims Crop species grown in a diversified crop rotation can influence soil N dynamics to varying degrees due to differences in the quantity and quality of the residues returned to the soil. The aim of this study was to quantify the contribution of N rhizodeposition by canola (Brassica napus L.) and pea (Pisum sativum L.) to the crop residue N balance and soil inorganic N pool. Methods Canola and pea were grown in a soil-sand mixture and were subject to cotton-wick ¹⁵N labeling in a greenhouse experiment. Nitrogen-15 recovered in the soil and roots were used to estimate N rhizodeposition. Results Belowground N, including root N and N rhizodeposits, comprised 70 % and 61 % of total crop residue N for canola and pea, respectively. Canola released the greatest amount of total root-derived N to the soil, which was related to greater root biomass production by canola. However, root-derived N in the soil inorganic N pool was greater under pea (13 %) than canola (4 %). Conclusions Our results show a significant belowground N contribution to total crop residue from pea and canola. Further investigation is required to determine whether input of the more labile N rhizodeposits of pea improves soil N supply to succeeding crops or increases the potential for N loss from the soil system relative to canola.